What Makes a Dangerous Goods Disaster? The Regulatory Perspective - van Schouwen, Jasmine (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2018)
The following study aims to identify the various regulatory failures which may lead to industrial disasters through the lens of a comparative study of the Fukushima Daiichi and Lac-Mégantic disasters. Through this comparison, the author aims to demonstrate that even in very different circumstances, certain common regulatory behaviours, structures and cultures may lead to similar disastrous outcomes. This study will focus on three types of regulatory failure: (1) weak or vague operating rules; (2) a lack of inspections to assess compliance with regulatory standards as well as a lack of enforcement when non-compliance is identified; and (3) regulatory capture resulting in the adoption of unsafe practices, underestimating risks or willful blindness to safety threats. However, the author emphasizes that other forms of regulatory failure, beyond the scope of this study, were present in both cases, including the regulators’ failure to keep track of essential safety data, the use of flawed risk assessment protocols, over-reliance on industry data, lack of independence from government, and failure to implement adequate emergency response programs.